Evaluasi Pembelajaran PAI Masa Pandemi Covid-19 di Fatih Bilingual School Kota Banda Aceh - Nora Hafiza (Tadabbur: Jurnal Peradaban Islam, 2021)
Evaluation in the teaching and learning process is an important component that cannot be separated from the entire learning process. Even in Islamic learning, teachers need to evaluate with the aim of measuring the level of success of students to be achieved in learning activities. However, during the outbreak of the Covid-19 virus in Indonesian territory, how can teachers still carry out the process of evaluating Islamic religious education learning in schools. SMA Fatih Bilingual School is one of the leading schools in Banda Aceh City which also implements online learning during the Covid-19 pandemic. This research is a descriptive-analytical qualitative research that aims to describe the process of planning, implementing, and evaluating Islamic religious education learning during the Covid-19 pandemic by examining data obtained from SMA Fatih Bilingual School, Banda Aceh City. Based on the theoretical study and the results of research in the field, the researcher concludes that the results of research on the evaluation of Islamic religious education learning during the Covid-19 pandemic at SMA Fatih Bilingual School Kota Banda Aceh are as follows: PAI learning evaluation is a series of activities in collecting various information systematically. That way, teachers can describe the ability of students during the learning process and can be used as a follow-up in making a decision in the future. The learning process during the Covid-19 pandemic is carried out through a hybrid learning system by combining blended learning strategies.